MOTIVASI BERPRESTASI ANTARA ATLET DAN NON ATLET - Rahayu Prasetiyo; Risfandi Setyawan; Novita Nur Synthiawati (Jurnal Pendidikan Olah Raga, 2023)
The purpose of this study was to determine differences in motivation for athletes and non-athletes. This study uses a comparative or comparative design. The sample in this study amounted to 142 people, with details of 72 elite athletes who are members of the East Java regional training center, and 70 non-athletes, namely students in the third year of the Physical Education Study Program at STKIP PGRI Jombang. Achievement motivation of athletes and non-athletes was measured using instruments developed by researchers with a validity value of 0.765 and a reliability of 0.954. data were analyzed using an independent test sample test, with the help of SPSS 24. The results showed a Sig value of 0.000 <0.05, differences in achievement motivation of elite athletes and non-athletes. Elite athletes show more enthusiasm to achieve achievements and overcome failure more quickly than non-athletes.